DSS Determines the Best Urban Village in handling COVID-19 Using AHP Method - Purba, Ramen Antonov (Jurnal Sistem Komputer dan Informatika (JSON), 2025)
This study aims to develop a Decision Support System (DSS) using the Analytic Hierarchy Process (AHP) method to determine the best-performing urban village in handling COVID-19 in Medan City, Indonesia. The research addresses the problem of the absence of a structured, data-driven evaluation model to objectively measure the performance of 151 urban villages across 21 sub-districts during the pandemic. Four criteria were used in the decision-making process: number of deaths, number of recovered patients, number of active cases, and the level of community compliance. The DSS, developed using a website-based programming language and integrated with the AHP method, generated weighted scores and ranked all evaluated villages. The results indicate that Harjosari I Village (A1), located in Medan Amplas Sub-district, achieved the highest overall score and was identified as the best urban village in handling COVID-19. System usability testing also produced very positive results, with Clarity of Instructions (90), Material Content (90), Discussion (93), and Interface Appearance (90), yielding an average score of 90 categorized as Very Adequate. This study contributes a validated web-based DSS model that supports objective evaluation, enhances transparency, and strengthens evidence-based decision-making for local governments in managing public health crises.